PENGARUH KONSENTRASI BIOURINE SAPI PADA SISTEM HIDROPONIK TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SAWI PAKCOY (Brassica Rapa L.) - Saputra, I Made Arya; Sujana, Putu; Suryana, I Made (Fakultas Pertanian dan Bisnis Universitas Mahasaraswati Denpasar, 2020)
Chemical pakcoy cultivation on agricultural land has a negative impact on the health of the human body, one of the solutions to overcome this is to use cow biourine organic material in the hydroponic system. Furthermore, a study was held entitled